Nilai-Nilai Pendidikan dalam Tradisi Islam Nusantara - Yayah, Yayah; Sumadi, Sumadi (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2017)
This article is motivated by the fact that various Islamic heritages are still well preserved through the expertise of the preachers in disseminating and introducing Islamic values into the nation of the archipelago with a very plural society consisting of dozens of ethnicities, with various cultures, traditions and beliefs as the largest Muslim country in world. Cultural history is a reflection of the life of mankind in the past in which there are various events of human life and the dynamics of its development from time to time concerning various aspects of life and culture. The review in this article uses interpretive methods through documentation studies. The results show that, the educational values contained in the Islamic Nusantara tradition are the value of religious education; value of moral education; value of social education; and the value of cultural education.